Pengaruh Kepuasan Kerja dan Komitmen Organisasi Terhadap Intention to Leave di Rumah Sakit Pura Raharja Surabaya - Muhammad Faris Rahmat Putra (Universitas Airlangga, 2017)
Turnover can be detrimented to the organization both in terms of cost, resources, and motivation of employees. The purpose is to determine the relationship variables on job satisfaction and commitment with the intention to leave. The method is an observational study with cross-sectional study. Samples from this study are employees Pura Raharja Hospital Surabaya who meet the criteria that respondents who are still within reach of researchers and respondents are willing to fill out a questionnaire study. Samples were calculated using simple random sampling and obtained by 50 respondents and the value of α = 0.05. The results of linear regression showed that the intention to leave the job is job satisfaction, career development job satisfaction and organizational commitment. The value of significance job satisfaction that is equal to 0,004 jobs, job satisfaction significant value that is equal to 0,04, career development and organizational commitment of significant value that is equal to 0.027. The variables that do not affect the intention to leave are a co-worker job satisfaction, job satisfaction wages, job satisfaction supervision and work commitments. The conclusion of this study is Job satisfaction affects the intention to leave and also commitments affect the intention to leave. Keywords: commitment, intention to leave, job satisfaction, turnover